The Ability of Computerized Accounting Information Systems in Saudi Public Universities to Face Cyber Threats - Kasasbeh, Feras Izzat Oqlah; Thuneibat, Nawaf Samah M. (International Review of Management and Marketing, 2018)
The study aimed at illustrating the history of cyber-attack experienced by Saudi Arabian organizations especially universities and overall cyber readiness. The study included 486 respondents from three different universities in Saudi Arabia. Survey was administered through printed copies of questionnaires. The data gathered were analyzed using IBM-SPSS software and AMOS plugin. Analysis revealed that participant's opinion regarding ability of the computerized accounting information system (CAIS) to face and safeguard against cyber threat depends on the awareness of the recent incidents of attack. Analysis showed that access control mediates the relationship between attack from malicious program and ability of the system to fend off those attacks. Better access control positively influences CAIS's ability to face threats. Author did not find any significant difference in people's perception across different demographic status regarding the Ability of CAIS to face Cyber Threat. Keywords: computerized accounting information system, CAIS, Cyber-attack, cyber security, cyber readiness, internet, malware. JEL Classifications: M21, M4, M1